مدى قدرة برامج التكوين التربوي والنفسي الجامعية على مواجهة بعض التحديات التي فرضتها العولمة دراسة ميدانية على عينة من طلاب كلية التربية في جامعة دمشق - عمار سام; قطيني فتون (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The present study aimed to determine the ability of educational and psychological creation programs in the university to confront some of the challenges imposed by globalization from the perspective of students of the Faculty of Education at the University of Damascus. The researcher followed the descriptive analytical method, using a questionnaire opinion as a tool for data collection,Thenumber of respondents reached (188) students. Results of the study showed that the most important challenges of globalization on the creationof the teacher in the Syrian Arab Republic,are: the challenge technological, cultural and social challenge, the challenge of maintaining the national identity, the challenge of science skills, and keep up with the challenge of global developments and updates. The results also showed that: the creationprograms proved to be better able to keep up with the cultural and social challenge, while the medium capacity to cope with the rest of the challenges,Therefore, the results showed the ability of creationprograms for the whole of these challenges was medium, as the results showed no significant statistical differences between the degrees of the sample respect to Variablesstage of study and Section, while statistically significant differences did not appear between educational qualification Diploma students, according to the variable Diploma Division (scientific / literary). The study came out a set of proposals, including:The attention to the technological process, and the creation of a special Curriculum of informing the teacher on the developments in the educational processIn addition providing the process of communication between the students of the Faculty of Education in the Syrian Arab Republic with their colleagues from other Arab and international universities, exchange of educational and scientific expertise. هدفت الدراسة الحالية إلى معرفة مدى قدرة برامج التكوين التربوي والنفسي الجامعية على مواجهة بعض التحديات التي فرضتها العولمة من وجهة نظر طلبة كلية التربية في جامعة دمشق. وقد اتبعت الباحثة المنهج الوصفي التحليلي، مستخدمةً استبانة رأي كأداة لجمع البيانات، وقد بلغ عدد أفراد العينة (188) طالباً وطالبةً. أظهرت نتائج الدراسة أن أهم التحديات التي تفرضها العولمة على عملية تكوين المعلم في الجمهورية العربية السورية هي: التحدي التقاني، والتحدي الثقافي والاجتماعي، تحدي الحفاظ على الهوية الوطنية، التحدي المتعلق بمهارات العلم، تحدي مواكبة التطورات والمستجدات العالمية. كما بينت النتائج أن برامج التكوين أثبتت أنها أكثر قدرة على مواكبة التحدي الثقافي والاجتماعي، في حين كانت متوسطة القدرة على مواجهة باقي التحديات، لذا جاءت النتائج الخاصة بقدرة برامج التكوين لمجمل هذه التحديات متوسطة، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية بين آراء أفراد العينة فيما يتعلق بمتغيري المرحلة الدراسية،والقسم الدراسي، بينما لم تظهر فروق ذات دلالة إحصائية بين طلاب دبلوم التأهيل التربوي وفقاً لمتغير شعبة الدبلوم (علمي/ أدبي). وقد خرجت الدراسة بمجموعة من المقترحات أهمها:الاهتمام بالجانب التقاني في عملية تكوين المعلم، وإيجاد مقرر خاص يتعلق بإطلاع الطالب- المعلم على مستجدات العملية التربوية من أفكار وآراء ونظريات، وكذلك تعرفهم بالمستجدات التكنولوجية التي تخدم العملية التربوية. بالإضافة إلى إتاحة عملية التواصل بين طلاب كلية التربية في الجمهورية العربية السورية مع زملائهم من الجامعات العربية والعالمية الأخرى، وذلك في نطاق تبادل الخبرات التربوية والعلمية. وإعادة النظر في البرامج الموجهة لطلاب دبلوم التأهيل التربوي لتكون قادرة على مراعاة تخصص الطالب- المعلم في مرحلة الإجازة الجامعية.